Empowers SD Muhammadiyah Sapen students to strengthen ear health and improve knowledge - Rizka Fakhriani; Fadli Robby Amsriza (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
The three parts of the ear are the external ear, middle ear, and inner ear. The ear contains cerumen, a natural material that protects the external ear canal. Proper ear hygiene and health are essential to prevent ear infections, ear ringing, hearing loss, and sudden deafness. In addition to improper ear cleaning, other factors might contribute to ear disorders, including the misuse of personal listening devices. SD Muhammadiyah Sapen students would be educated on the significance of maintaining ear health through this service project. This community service activity is conducted online via mini-webinars or counseling using zoom meetings, presentations, educational films, and brochures on how to maintain ear health. This extension is quasi-experimental, with a pre-and post-test design involving a single group, utilizing the Paired Samples T-Test model for data analysis. The activity commences with a pre-test administered to students, continues with the presentation of information, discussion, and question-and-answer sessions, and concludes with a post-test designed to assess students' level of knowledge and the activity's success. Twenty students participated in this community service event. Conclusion: There is a significant difference between the average pre-test and post-test scores with a p-value of 0.01 (0.05).